Joseph Davidovich Levit – the oretician and practitioner of national endocrinology (90th birthday anniversary) - Shmuel Levit; Vyacheslav Moiseevich Levit (Сахарный диабет)
Joseph Davidovich Levit – a well-known Soviet endocrinologist; a disciple of the founder of the Russian school of endocrinology, Vasily Gavrilovich Baranov; and an outstanding thyroidologist whose name is firmly established in the history of medicine.Dr. Joseph Levit was among the pioneers of the field. Not only did he meticulously research the endemic problems of goiter and its various forms, but also showed a clear inverse relationship between autoimmune thyroiditis (AIT) and endemic iodine deficiency.He was one of the first in the Soviet Union to open a hormone laboratory built to the highest standards at the time, and put into practice the prevention and treatment of various forms of goiter. He saved tens of thousands of patients from the necessity of surgical intervention, was categorically against the extirpation of the thyroid gland in AIT patients, a common practice in those days.A brilliant organizer, he founded from scratch the endocrine service in the Chelyabinsk region, considered one of the best in the USSR.Trained countless experts – endocrinologists, post-graduates and doctors of sciences.Dr. Levit authored over 100 scientific papers, the monograph “Autoimmune Thyroiditis”, and numerous innovations. He held a strong belief in the possibility of bringing autoimmune diseases into remission and was far ahead of his time proving it in practice.The main works of Dr. Joseph Levit, as well as his scientific biography may serve not only as a source of useful information, but also as an incentive for independent research for both the younger generation and the seasoned experts in various fields of medical science.